2017
DOI: 10.1590/2359-3997000000227
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of salivary oxidative parameters in overweight and obese young adults

Abstract: Background: Obesity is characterized by a deposition of abnormal or excessive fat in adipose tissue, and is linked with a risk of damage to several metabolic and pathological processes associated with oxidative stress. To date, salivary oxidative biomarkers have been minimally explored in obese individuals. Thus, the aim of this study was to assess the concentrations of salivary oxidative biomarkers (ferric-reducing antioxidant power, uric acid, sulfhydryl groups) and lipid peroxidation in obese and overweight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 41 publications
3
10
1
Order By: Relevance
“…Therefore, further researches are necessary for this area, since the salivary biomarkers seem to be a promising diagnostic material, because it is easily accessible and non-expensive. Furthermore, salivary redox biomarkers are used in the diagnosis of metabolic diseases [19][20][21][22][23][24][117][118][119][120][121] or cancer [122].…”
Section: Summary and Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, further researches are necessary for this area, since the salivary biomarkers seem to be a promising diagnostic material, because it is easily accessible and non-expensive. Furthermore, salivary redox biomarkers are used in the diagnosis of metabolic diseases [19][20][21][22][23][24][117][118][119][120][121] or cancer [122].…”
Section: Summary and Perspectivementioning
confidence: 99%
“…However, among all of the biomarkers measured in saliva, it is the indicators of oxidative stress that are becoming increasingly popular. Interestingly, the results of recent studies indicate the high diagnostic value of salivary redox parameters in the diagnosis of obesity [19,20], insulin resistance [21,22], chronic kidney disease [23,24], but also neurodegenerative diseases (NDDs) [1,25,26]. Indeed, salivary antioxidants, as well as products of protein, lipid, and DNA oxidation, are proposed as potential diagnostic biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that obesity results in the dysfunction of salivary glands as well as changes in salivary flow and composition [15][16][17]35]. As saliva is essential for maintaining appropriate functions of the body, such as swallowing, chewing, carbohydrate digestion, healing of the oral mucosa and tooth enamel remineralization, it is not surprising that excessive body weight increases the risk of gingivitis [36], periodontitis [37], caries [38,39] and inflammatory changes in the oral cavity mucosa [40].…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of salivary gland lesions in the course of obesity is not fully understood, although the influence of OS is emphasized. It has been demonstrated that adult morbid obesity is associated with disorders of antioxidant systems [15,16] and oxidative damage to salivary proteins, lipids, and DNA [17], while bariatric treatment generally lowers the levels of salivary oxidative damage. However, it does not rescue antioxidant capacity of non-stimulated and stimulated saliva [16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation